KOMUNIKASI, INFORMASI, DAN EDUKASI (KIE) MEDIA FLASH CARD EFEKTIF MENINGKATKAN PERSEPSI IMUNISASI HPV - Marlinda, Marlinda; Tussellawati, Hani; Madiyanti, Desi Ari (Jurnal Ilmiah Keperawatan IMELDA, 2024)
The Human Papilloma Virus (HPV) vaccination is a primary prevention measure against cervical cancer. However, the dissemination of information regarding HPV vaccination has not been optimal, leading to negative perceptions among couples of reproductive age about this vaccination. Therefore, the delivery of information through Communication, Information, and Education (CIE) requires the use of appropriate media. This study aims to determine the effect of CIE using flash card media on perceptions of HPV vaccination implementation in Kresnowidodo Urban Village. The design used is a quasi-experimental with a non-randomized control group pretest-posttest design, involving 15 respondents in the intervention group and 15 respondents in the control group from the Family Welfare Empowerment group in Kresnowidodo Urban Village. The instruments used are flash cards and questionnaires, with data analysis using the Wilcoxon test. The study results show a significant effect of CIE using flash card media on the perception of HPV vaccination implementation, with a p-value of 0.022 (p < 0.05). The small, portable flash cards with pictures help improve the understanding of couples of reproductive age about the importance of HPV vaccination. It is recommended that couples of reproductive age get the HPV vaccination as a preventive measure against cervical cancer.